Developing A Scale To Assess The Acquisition Of Language Skills For Academic Purposes: An Applied Study On Students Of The Institute Of Arabic Language Teaching For Non-Native Speakers At The Islamic University/ بناء مقياس لبيان مدى اكتساب المهارات اللغوية لأغراض أكاديمية دراسة تطبيقية على طلاب معهد تعليم اللغة العربية لغير الناطقين بها بالجامعة الإسلامية - Khalid A. Alharbi (Ijaz Arabi Journal of Arabic Learning, 2026)
This study aims to construct a scale to measure the acquisition of academic language skills among students of the Arabic Language Institute for Non-Native Speakers at the Islamic University. The significance of the research lies in the difficulties international students face in understanding their courses, especially when dealing with specialized academic terminology in fields such as statistics and research methodology. The study proposes a comprehensive scale covering the four main skills (listening, speaking, reading, and writing), to serve as a diagnostic tool that supports the improvement of instructional programs and aligns them with students’ academic needs. The research is delimited to the students of the Institute at the Islamic University during the academic years 1442–1446 AH. A scale was developed to assess academic language skills (listening, writing, reading, speaking) among students at the Islamic University of Madinah. The scale was validated and applied to a sample of 50 students. The results showed that students achieved varying levels of proficiency across the four skills. Listening: strong performance in summarizing (90%), moderate performance in understanding relationships and memory (62%–76%), lower performance in appreciation and interaction (20%–52%). Writing: moderate performance (52%–58%). Reading: moderate to good performance (60%–81%). Speaking: moderate performance (61.2%–62.4%).